(Math Added)
Line 18: Line 18:
 
----
 
----
 
----
 
----
[Math goes here]
+
In this slecture, we are going to look at the continuous-time fourier transforms of the <math>comb_T()</math> and <math>rep_T()</math> functions.
----
+
 
 +
 
 +
First, we will define the a function <math>p_T(t)</math> as pulse train function, or series of time-shifted impulses:
 +
 
 +
<math>
 +
\begin{align}
 +
p_T(t) = \sum_{n=-\infty}^{\infty}\delta(t-kT)
 +
\end{align}
 +
</math>
 +
 
 +
Now let's take a look at the <math>comb_T()</math> function. By definition:
 +
 
 +
 
 +
<math>\begin{align}comb_T(x(t)) :&= x(t)p_T(t) \\
 +
&= x(t)\sum_{k=-\infty}^{\infty}\delta(t-kT) \\
 +
&= \sum_{k=-\infty}^{\infty}x(t)\delta(t-kT) \\
 +
&= \sum_{k=-\infty}^{\infty}x(kt)\delta(t-kT) \end{align}</math><br>
 +
 
 +
 
 +
The result of this function is a set of time-shifted impulses whose amplitudes match those of the input signal x(t) at each given point. This signal can be referred to as a sampling of x(t) with a sampling rate of 1/T.
 +
 
 +
Before we get started with the fourier transform of this function, lets take a look at the <math>rep_T()</math> function, which is very similar to the <math>comb_T()</math> function:
 +
 
 +
<math>\begin{align}rep_T(x(t)) :&= x(t)*p_T(t) \\
 +
&= x(t)*\sum_{k=-\infty}^{\infty}\delta(t-kT) \\
 +
&= \sum_{k=-\infty}^{\infty}x(t)*\delta(t-kT) \\
 +
&= \sum_{k=-\infty}^{\infty}x(t-kT)\end{align} </math><br>
 +
 
 +
As shown above, the <math>rep_T()</math> function differs from the <math>comb_T()</math> function in that it convolves the input signal with the pulse train rather than simply multiplying the two.
 +
 
 +
Now that we've seen the <math>rep_T()</math> function, we can go back to the fourier transform of the <math>comb_T()</math> function:
 +
 
 +
<math>{\mathcal F}(comb_T(x(t))) = {\mathcal F}(x(t)p_T(t))</math>
 +
 
 +
Using the multiplication property:
 +
 
 +
<math>\begin{align} &= {\mathcal X}(f)*{\mathcal F}(p_T(t)) \\
 +
&= {\mathcal X}(f)*{\mathcal F}(\sum_{n=-\infty}^{\infty}\frac{1}{T}e^{j{\frac{2 \pi}{T}}nt}) \\
 +
&= {\mathcal X}(f)*\sum_{n=-\infty}^{\infty}\frac{1}{T}{\mathcal F}(e^{j{\frac{2 \pi}{T}}nt}) \\
 +
&= {\mathcal X}(f)*\frac{1}{T}\sum_{n=-\infty}^{\infty}\delta(f - \frac{n}{T}) \\
 +
&= \frac{1}{T}{\mathcal X}(f)*{\mathcal P}_{\frac{1}{T}}(f)\end{align}</math><br>
 +
 
 +
Now, knowing that a signal convolved with a pulse train results in a <math>rep_T()</math> function, we can simplify this as:
 +
 
 +
<math>{\mathcal F}(comb_T(x(t))) = \frac{1}{T}rep_{\frac{1}{T}}({\mathcal X}(f))</math>
 +
 
 +
Simply put, the fourier transform of a comb function is a rep function. Now let's see if the inverse is true:
 +
 
 +
<math>{\mathcal F}(rep_T(x(t))) = {\mathcal F}(x(t)*p_T(t))</math>
 +
 
 +
Using the convolution property:
 +
 
 +
<math>\begin{align} &= {\mathcal X}(f){\mathcal F}(p_T(t)) \\
 +
&= {\mathcal X}(f){\mathcal F}(\sum_{n=-\infty}^{\infty}\frac{1}{T}e^{j{\frac{2 \pi}{T}}nt}) \\
 +
&= {\mathcal X}(f)\sum_{n=-\infty}^{\infty}\frac{1}{T}{\mathcal F}(e^{j{\frac{2 \pi}{T}}nt}) \\
 +
&= {\mathcal X}(f)\frac{1}{T}\sum_{n=-\infty}^{\infty}\delta(f - \frac{n}{T}) \\
 +
&= {\mathcal X}(f)\frac{1}{T}{\mathcal P}_{\frac{1}{T}}(f) \\
 +
&= \frac{1}{T}comb_{\frac{1}{T}}({\mathcal X}(f))\end{align}</math><br>
 +
 
 +
As shown above, we now know that the fourier transform of a rep is comb.
 
----
 
----
 
----
 
----

Revision as of 17:58, 1 October 2014


ftrepcomb_mattmiller

Fourier Transform of Rep and Comb Functions

A slecture by ECE student Matt Miller

Partly based on the ECE438 Fall 2014 lecture material of Prof. Mireille Boutin.



In this slecture, we are going to look at the continuous-time fourier transforms of the $ comb_T() $ and $ rep_T() $ functions.


First, we will define the a function $ p_T(t) $ as pulse train function, or series of time-shifted impulses:

$ \begin{align} p_T(t) = \sum_{n=-\infty}^{\infty}\delta(t-kT) \end{align} $

Now let's take a look at the $ comb_T() $ function. By definition:


$ \begin{align}comb_T(x(t)) :&= x(t)p_T(t) \\ &= x(t)\sum_{k=-\infty}^{\infty}\delta(t-kT) \\ &= \sum_{k=-\infty}^{\infty}x(t)\delta(t-kT) \\ &= \sum_{k=-\infty}^{\infty}x(kt)\delta(t-kT) \end{align} $


The result of this function is a set of time-shifted impulses whose amplitudes match those of the input signal x(t) at each given point. This signal can be referred to as a sampling of x(t) with a sampling rate of 1/T.

Before we get started with the fourier transform of this function, lets take a look at the $ rep_T() $ function, which is very similar to the $ comb_T() $ function:

$ \begin{align}rep_T(x(t)) :&= x(t)*p_T(t) \\ &= x(t)*\sum_{k=-\infty}^{\infty}\delta(t-kT) \\ &= \sum_{k=-\infty}^{\infty}x(t)*\delta(t-kT) \\ &= \sum_{k=-\infty}^{\infty}x(t-kT)\end{align} $

As shown above, the $ rep_T() $ function differs from the $ comb_T() $ function in that it convolves the input signal with the pulse train rather than simply multiplying the two.

Now that we've seen the $ rep_T() $ function, we can go back to the fourier transform of the $ comb_T() $ function:

$ {\mathcal F}(comb_T(x(t))) = {\mathcal F}(x(t)p_T(t)) $

Using the multiplication property:

$ \begin{align} &= {\mathcal X}(f)*{\mathcal F}(p_T(t)) \\ &= {\mathcal X}(f)*{\mathcal F}(\sum_{n=-\infty}^{\infty}\frac{1}{T}e^{j{\frac{2 \pi}{T}}nt}) \\ &= {\mathcal X}(f)*\sum_{n=-\infty}^{\infty}\frac{1}{T}{\mathcal F}(e^{j{\frac{2 \pi}{T}}nt}) \\ &= {\mathcal X}(f)*\frac{1}{T}\sum_{n=-\infty}^{\infty}\delta(f - \frac{n}{T}) \\ &= \frac{1}{T}{\mathcal X}(f)*{\mathcal P}_{\frac{1}{T}}(f)\end{align} $

Now, knowing that a signal convolved with a pulse train results in a $ rep_T() $ function, we can simplify this as:

$ {\mathcal F}(comb_T(x(t))) = \frac{1}{T}rep_{\frac{1}{T}}({\mathcal X}(f)) $

Simply put, the fourier transform of a comb function is a rep function. Now let's see if the inverse is true:

$ {\mathcal F}(rep_T(x(t))) = {\mathcal F}(x(t)*p_T(t)) $

Using the convolution property:

$ \begin{align} &= {\mathcal X}(f){\mathcal F}(p_T(t)) \\ &= {\mathcal X}(f){\mathcal F}(\sum_{n=-\infty}^{\infty}\frac{1}{T}e^{j{\frac{2 \pi}{T}}nt}) \\ &= {\mathcal X}(f)\sum_{n=-\infty}^{\infty}\frac{1}{T}{\mathcal F}(e^{j{\frac{2 \pi}{T}}nt}) \\ &= {\mathcal X}(f)\frac{1}{T}\sum_{n=-\infty}^{\infty}\delta(f - \frac{n}{T}) \\ &= {\mathcal X}(f)\frac{1}{T}{\mathcal P}_{\frac{1}{T}}(f) \\ &= \frac{1}{T}comb_{\frac{1}{T}}({\mathcal X}(f))\end{align} $

As shown above, we now know that the fourier transform of a rep is comb.



(create a question page and put a link below)

Questions and comments

If you have any questions, comments, etc. please post them on this page.


Back to ECE438, Fall 2014

Alumni Liaison

To all math majors: "Mathematics is a wonderfully rich subject."

Dr. Paul Garrett